2013
DOI: 10.1096/fasebj.27.1_supplement.688.7
|View full text |Cite
|
Sign up to set email alerts
|

Aging‐induced dysregulation of Dicer1‐dependent microRNA expression impairs angiogenic capacity of rat cerebromicrovascular endothelial cells

Abstract: Age‐related impairment of angiogenesis is likely to play a central role in cerebromicrovascular rarefaction and development of vascular cognitive impairment. To test the hypothesis that dysregulation of Dicer1 impairs endothelial angiogenic capacity in aging, primary cerebromicrovascular endothelial cells(CMVEC) were isolated from young (3 mo) and aged (24 mo) F344xBN rats. In aged CMVECs Dicer1 was down‐regulated and its expression was increased by treatment with PEG‐catalase. Compared to young cells aged CMV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…6d ). The stability of Dicer which is critical to miRNA expression in the brain [83, 84, 103, 104] is sensitive to ROS and interferons (IFNs) [105, 106] and most of its expression in the brain is lost during aging [85]. During AD Aβ plaques cause further upregulation of ROS and induce inflammation resulting in elevated IFNs ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…6d ). The stability of Dicer which is critical to miRNA expression in the brain [83, 84, 103, 104] is sensitive to ROS and interferons (IFNs) [105, 106] and most of its expression in the brain is lost during aging [85]. During AD Aβ plaques cause further upregulation of ROS and induce inflammation resulting in elevated IFNs ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…One explanation for this finding may be due to an overall reduction in protein translation among the late passage, senescent cells, or dysfunctional translational "machinery." Recent studies have shown that global protein translation is reduced among senescent cells, and Dicer expression and activity is likewise dysfunctional (58)(59)(60). Glucose stress may accelerate or enhance this age-associated protein translation dysfunction.…”
Section: Glucose Stress Induces Transcriptional Dysregulation Of Nosmentioning
confidence: 99%
“…Since the p53 signaling pathway is among the top pathways highlighted by our Gene Ontology analysis (Table 2), p53 could be responsible for the global downregulation of miRNAs through a negative feedback loop mechanism. In a previous study, exogenous H 2 O 2 exposure has been shown to cause a significant decrease in Dicer expression resulting in the downregulation of 89% of microRNAs that are normally expressed in endothelial cells (Ungvari et al, 2013).…”
Section: Discussionmentioning
confidence: 98%